Mulheres nas ondas das energias renováveis - Bezerra, Carlos André Dias (2018)
Industries of photovoltaic panels, wind turbines and other renewable energy sources are being installed in Brazil in recent years, mainly due to incentive policies energy production coming from renewable sources. However, it has not been subject to the same rate in manpower training, development of equipment and processes to support these industries or even the exploitation of renewable resources with national technology. On the other hand the Brazilian government has been concerned about the little training of women to careers in sciences, engineering and computing and with the evasion that occurs in the early years of these courses, leading the government to encourage projects that stimulate the vocational interest female students of high school and undergraduate for such professions, and the scientific and technological research. Why not use renewable energy to reawaken the vocation for engineering in high school students, doing what they like: apply in practice the theory? Why not use the undergraduate courses students as instructors? This paper deals with the methodology used in the project that used the hands on approach to design and implement a similar prototype to those used for generating electricity from the motion of the waves, allowing the application of high school content on this design under the guidance of students of engineering courses. The reduction of university dropout was also attacked by involving the undergraduate students with the methodology employed. Therefore, this article aims to present the work methodology to include high school students, and students freshmen of engineering course, the development of a similar prototype to those used to generate electricity, such as vocational guidance factor and motivator for admission in undergraduate courses in sciences, engineering and computing, by the high school students, and continuity in engineering by the university. This work was divided into seven steps: Team training, theoretical basement team, technical training of staff, training to build the prototype, manufacture and construction of prototypes, testing at sea (beach) and publicize of the project. The Co-executing institution of the project was the State Preparatory High School Ronaldo Caminha Barbosa, who is a public school run by the Ceara State Government. The main results were: lectures in High School and Mechanical Engineering Course; integration of high school students on the premises of a university laboratory; conception, design, manufacture and assembly of prototypes; technical visits to school, university and wave energy park; seminars and short courses on engineering and wave energy; training in prototype assembly; vocational guidance for public high school students; fixing undergraduate students in engineering course; and testing the prototype.